Phenotypic diversity of Menkes disease in mottled mice is associated with defects in localisation and trafficking of the ATP7A protein - Kim, Byung‐Eun (BMJ Group, 2007)
Owing to mutations in the copper‐transporting P‐type ATPase, ATP7A (or MNK), patients with Menkes disease (MD) have an inadequate supply of copper to various copper‐dependent enzymes. The ATP7A protein is located in the trans‐Golgi network, where it transports copper via secretory compartments to copper‐dependent enzymes. Raised copper concentrations result in the trafficking of ATP7A to the plasma membrane, where it functions in copper export. An important model of MD is the Mottled mouse, which possesses mutations in Atp7A. The Mottled mouse displays three distinct phenotypic severities: embryonic lethal, perinatal lethal and a longer‐lived viable phenotype. However, the effects of mutations from these phenotypic classes on the ATP7A protein are unknown. In this study, we found that these classes of mutation differentially affect the copper transport and trafficking functions of the ATP7A protein. The embryonic lethal mutation, Atp7a(mo11H) (11H), caused mislocalisation of the protein to the endoplasmic reticulum, impaired glycosylation, and abolished copper delivery to the secretory pathway. In contrast, the perinatal lethal and viable mutations, Atp7a(moMac) (Macular) and Atp7a(moVbr) (Viable brindle) both resulted in a reduction in copper delivery to the secretory pathway and constitutive trafficking of the ATP7A protein to the plasma membrane in the absence of additional copper. In the case of Viable brindle, this hypertrafficking response was dependent on the catalytic phosphorylation site of ATP7A, whereas no such requirement was found for the Macular mutation. These findings provide evidence that the degree of MD severity in mice is associated with both copper transport and trafficking defects in the ATP7A protein.